The Impact of Artificial Intelligence on Legal Decision-Making: Ethical and Practical Implications - Syamsul Bahri; Siri Lek; Aom Thai (Yayasan Adra Karima Hubbi, 2026)
Background. (The increasing adoption of artificial intelligence (AI) within legal systems has significantly transformed how legal decisions are supported, formulated, and justified. AI-driven tools are now used in areas such as risk assessment, case prioritization, sentencing support, and legal analytics, raising fundamental ethical and practical concerns regarding transparency, fairness, and accountability. Purpose. This study aims to examine the impact of AI on legal decision-making processes by analyzing both its operational benefits and its ethical implications within contemporary legal institutions. Method. The research employs a qualitative–analytical design that integrates doctrinal legal analysis, ethical evaluation, and empirical examination of documented AI-assisted legal practices. Data were collected from secondary legal sources, policy documents, case studies, and expert analyses to identify patterns of AI influence on judicial reasoning and institutional behavior. Results. The findings reveal that AI-assisted decision-making enhances procedural efficiency and consistency, particularly in high-volume legal contexts, but simultaneously introduces challenges related to opacity, automation bias, and diminished explainability. Conclusion. The study concludes that AI functions as a powerful decision-support instrument that reshapes legal reasoning while remaining dependent on human oversight for legitimacy and justice. Effective integration of AI in legal decision-making requires robust ethical frameworks, transparent governance mechanisms, and sustained human responsibility to ensure that technological advancement supports, rather than undermines, fundamental legal values.